Synthesis, crystal structure and luminescence properties of a new samarium borate phosphate, CsNa2Sm2(BO3)(PO4)2. Issue 12 (13th November 2020) - Zhao, Dan; Shi, Lin-Ying; Zhang, Rui-Juan; Xue, Ya-Li
Abstract : The crystal structure of CsNa2 Sm2 (BO3 )(PO4 )2 is reported, together with its orange‐light‐emitting properties with an optimized Sm 3+ concentration by doping with a Gd 3+ component. Abstract : A new caesium sodium samarium borate phosphate, CsNa2 Sm2 (BO3 )(PO4 )2, has been obtained successfully by the high‐temperature solution growth (HTSG) method and single‐crystal X‐ray diffraction analysis reveals that it crystallizes in the orthorhombic space group Cmcm . The structure contains BO3, PO4, NaO7 and SmO7 polyhedra which are interconnected via corner‐ or edge‐sharing O atoms to form a three‐dimensional [Na2 Sm2 (BO3 )(PO4 )2 ]∞ network. This network delimits large cavities where large Cs + cations reside to form the total structure. Under 402 nm light excitation, CsNa2 Sm2 (BO3 )(PO4 )2 exhibits three emission bands due to the 4 f →4 f transitions of Sm 3+ . Furthermore, we introduced Gd 3+ into Sm 3+ sites to optimize the Sm 3+ concentration and improve the luminescence intensity. The optimal concentration is Gd/Sm = 98/2. The luminescent lifetime of a series of CsNa2 Gd2(1– x ) Sm2 x (BO3 )(PO4 )2 phosphors shows a gradual degradation of lifetime from 2.196 to 0.872 ms for x = 0.01–0.10. The Commission Internationale de l'Eclairage (CIE) 1931 calculation reveals that CsNa2 Gd1.96 Sm0.04 (BO3 )(PO4 )2 can emit orange light under 402 nm excitation.